2013
DOI: 10.3389/fncom.2013.00163
|View full text |Cite
|
Sign up to set email alerts
|

Motor thalamus integration of cortical, cerebellar and basal ganglia information: implications for normal and parkinsonian conditions

Abstract: Motor thalamus (Mthal) is implicated in the control of movement because it is strategically located between motor areas of the cerebral cortex and motor-related subcortical structures, such as the cerebellum and basal ganglia (BG). The role of BG and cerebellum in motor control has been extensively studied but how Mthal processes inputs from these two networks is unclear. Specifically, there is considerable debate about the role of BG inputs on Mthal activity. This review summarizes anatomical and physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
210
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(219 citation statements)
references
References 286 publications
(485 reference statements)
8
210
0
1
Order By: Relevance
“…Similar decreases in firing rates were found in several previous studies, including Parkinsonian patients (Chen et al 2010;Molnar et al 2005), MPTP-treated cats (Schneider and Rothblat 1996), and 6-hydroxydopamine (6-OHDA)-lesioned rats (Ni et al 2000). However, other studies found either no change in thalamic firing activity in MPTP-treated monkeys (Pessiglione et al 2005) or increases in firing in 6-OHDA-treated rats (Bosch-Bouju et al 2014). The discrepancies between these studies may be related to species and experimental differences across studies, such as the specific cell types selected for recording, the state of wakefulness of the animals, or the severity of Parkinsonism.…”
Section: Mptp-induced Changes Of Thalamic Activitymentioning
confidence: 47%
See 1 more Smart Citation
“…Similar decreases in firing rates were found in several previous studies, including Parkinsonian patients (Chen et al 2010;Molnar et al 2005), MPTP-treated cats (Schneider and Rothblat 1996), and 6-hydroxydopamine (6-OHDA)-lesioned rats (Ni et al 2000). However, other studies found either no change in thalamic firing activity in MPTP-treated monkeys (Pessiglione et al 2005) or increases in firing in 6-OHDA-treated rats (Bosch-Bouju et al 2014). The discrepancies between these studies may be related to species and experimental differences across studies, such as the specific cell types selected for recording, the state of wakefulness of the animals, or the severity of Parkinsonism.…”
Section: Mptp-induced Changes Of Thalamic Activitymentioning
confidence: 47%
“…The borders between the cerebellar-and the basal ganglia-receiving territories are interdigitating; however, the cerebellar-and basal ganglia-receiving thalamic cells are distinct in primates [for review, see Bosch-Bouju et al (2013)]. The overlap should not be a concern for the present study, because almost all cells included in the presented analysis were at least 0.5 mm away from the border between the cerebellar and basal ganglia territories, as defined in Lanciego's atlas (Lanciego and Vazquez 2012).…”
Section: Potential Study Limitationsmentioning
confidence: 90%
“…21,22 All of these aspects are particularly important to the functioning of the thalamocortical network, a brain structure implicated in motor-related activities. [23][24][25][26] In the present study, we analyzed the functional expression of the 2 ALS-associated missense mutations in Ca v 3.2 channels. We show that both mutations produce significant alterations on the channel activity, consistent with a loss of channel function.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in non-human primates have shown that the thalamic ventrobasal complex (the caudal division of the VPL nucleus and the large-celled part of the ventroposteromedial nucleus) project to primary and secondary somatosensory areas (S1 and S2) [10]. The ventral lateral and ventral anterior nuclei project to primary motor cortex (M1) and premotor cortex [10].…”
Section: Introductionmentioning
confidence: 99%